2019
DOI: 10.1634/theoncologist.2019-io-s1-s01
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Hepatocellular Carcinoma: Opportunities and Challenges

Abstract: This review focuses on the opportunities and challenges of immune checkpoint inhibitor therapies for hepatocellular carcinoma, especially hepatitis B virus‐related hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 83 publications
0
97
0
1
Order By: Relevance
“…Currently, the tyrosine kinase inhibitors (TKI) sorafenib and lenvatinib are the first-line treatments in advanced HCC [5][6][7][8]. Regorafenib, nivolumab, cabozantinib, and ramucirumab were approved as second line therapies following their recent successes in several clinical trials [9][10][11][12][13][14][15]. Despite these breakthroughs, many patients still do not survive advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the tyrosine kinase inhibitors (TKI) sorafenib and lenvatinib are the first-line treatments in advanced HCC [5][6][7][8]. Regorafenib, nivolumab, cabozantinib, and ramucirumab were approved as second line therapies following their recent successes in several clinical trials [9][10][11][12][13][14][15]. Despite these breakthroughs, many patients still do not survive advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
“…These immunological features enable HCC to benefit from immunotherapy. Thus, harnessing these immune characters through combination immunotherapy is proposed as the next important step in treatment of advanced HCC [4,[13][14][15]21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors such as antibodies against PD-L1 and PD-1 have been introduced into clinical practice for a number of cancers [117,118]. In HCC, double-blind randomized clinical trials studies have shown that immune checkpoint inhibitor therapy can provide favorable responses in patients with advanced HCC [119]. However, recent results from phase III CheckMate 459 and KEYNOTE-240 studies of PD-1-targeted antibodies for advanced HCC did not achieve statistical significance or superiority in the overall survival in comparison to sorafenib [120,121].…”
Section: Exosomal Mirnas' Future Implications For Immunotherapy In Hccmentioning
confidence: 99%
“…A small retrospective analysis noted that treatment with TKIs then immunotherapy then TKIs appears to be safe, and some patients did derive added benefits, but the data are too preliminary to draw any conclusions [49]. An excellent review article published in 2019 listed all the current ongoing trials involving checkpoint inhibitors; many are utilizing a combination approach [50]. We are eagerly awaiting these trial results to determine if any particular combination proves to be more effective than others.…”
Section: Immune-check Point Inhibitorsmentioning
confidence: 99%